2016
DOI: 10.1590/1984-70332016v16n4n51
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between fruit traits and contents of ascorbic acid and carotenoids in peach

Abstract: This study aimed to evaluate the relationship between fruit traits and their direct and indirect effects on the content of ascorbic acid and carotenoids in peaches and nectarines. The traits fruit mass (FM); equatorial diameter (ED); suture diameter (SD); polar diameter (PD); pulp firmness (FIR); soluble solids (SS); titratable acidity (TA); SS/TA ratio; contents of ascorbic acid (AA) and carotenoids (CT); and skin and pulp color were evaluated in 28 peach cultivars, and two nectarine cultivars. The phenotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
2
7
0
1
Order By: Relevance
“…The carotenoid content in plants depends on, among other factors, the genetic variety, ripening stage, post-harvest storage, and processing (Llorente, Garcia, Stange, & Concepcion, 2017, Matias et al, 2016a. Matias et al (2016b) noted that the concentration of total carotenoid contents accounted for the yellow coloration of the pulp and Faraoni, Ramos, Stringheta, and Laureano (2008) mentioned that in the pulp and by-products, the color, besides influencing quality, is an important parameter used for the quality control of these products.…”
Section: Resultsmentioning
confidence: 99%
“…The carotenoid content in plants depends on, among other factors, the genetic variety, ripening stage, post-harvest storage, and processing (Llorente, Garcia, Stange, & Concepcion, 2017, Matias et al, 2016a. Matias et al (2016b) noted that the concentration of total carotenoid contents accounted for the yellow coloration of the pulp and Faraoni, Ramos, Stringheta, and Laureano (2008) mentioned that in the pulp and by-products, the color, besides influencing quality, is an important parameter used for the quality control of these products.…”
Section: Resultsmentioning
confidence: 99%
“…The need for reliable data about carotenoids in foods is widely recognized in various fields of study. The factors that make this analysis difficult include the large number of carotenoids naturally existing, the qualitative and quantitative variation of these foods, the little amount of pro-vitamin A carotenoids, its varied biopotency and the fact of the carotenoids are extremely unsaturated molecules, providing isomerisation processes, oxidation and degradation during the analysis (Matias et al, 2016). According Silva, Cremasco, Matias, Silva, and Bruckner (2014), the levels of total carotenoids concentration characterizes the yellow coloration of the pulp and in accordance with Faraoni, Ramos, and Stringheta (2008), in the pulp and products produced on the basis of fruit pulp, the color is an important parameter used in quality control of these products.…”
Section: Discussionmentioning
confidence: 99%
“…The high instability of vitamins and pro-vitamins, during the ripening of fruits can result in significant changes in the qualitative and quantitative composition of some nutrients (Matias et al, 2016). According to Silva et al (2014) during the fruits ripening it may occur nutrient losses depending on the environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The quality attributes that have greater relevance in fruits are: color, firmness, soluble solids content, acidity and sugars: acids ratio (MATIAS et al, 2017;MATIAS et al, 2016;SILVA et al, 2016). Fischer et al (2012a) reported that high quality fruits require an adequate relationship between leaves and fruits.…”
Section: Introductionmentioning
confidence: 99%